Self-Healing in Gen-Z Adolescents’: Behind the Scene of Social Media - Noviar, Tri Nur Aini; Az Zahra, Amanda Fatimah; Putra, Raditya Pratama; Rachmawati, Indri; Silfiani, Indri; Dewi, Rizki Anggita (Universitas Muhammadiyah Yogyakarta, 2025)
This descriptive quantitative research aims to explore adolescents’ understanding of stressors arising from social media use, their self-actualization through social media, motivation for self-healing, and the role of spirituality and communication as a means to overcome stress. Primary data were collected through questionnaires distributed to 73 adolescents, while secondary data were obtained via interviews with psychologists, counseling teachers, and ustazds (religious teachers). The results indicate that (1) social media is not the primary stressor for adolescents; the most significant stressors were family problems (71.2%), academic challenges (60.3%), and parental demands (54.8%); (2) Generation Z shows limited interest in openly self-actualizing on social media; (3) 63.01% of respondents are motivated to seek self-healing information via social media; and (4) spirituality and communication serve as effective mediums for adolescents to manage and overcome stress